PERBANDINGAN HASIL PEMERIKSAAN Hb IBU HAMIL MENGGUNAKAN Hb SAHLI DAN EASY TOUCH GHb DI BPS SULIS DESA GRINTING KABUPATEN BREBES TAHUN 2011 - Sugi Purwanti; Inke Puspita Maris (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT Anemia was a condition in which the levels of Hb and or erythrocyte count was lower than normal value. Hemoglobin was an oxygen transporting proteida that serves to spread throughout the body. Examination of Hb levels of pregnant women could be done with several methods of examination, by using such means Hb Sahli and Easy Touch GHB. to know the comparison of results of examinations of pregnant women with Hb Sahli and Hb Easy Touch GHb in BPS Sulis Village District Grinting Bulakamba Brebes in 2011.The research method would be used was a descriptive cross-sectional comparative approach. The population in this study were pregnant women in Connecticut Sulis Village District Grinting Bulakamba Brebes. Engineering samples were used was purposive sampling with a measuring tool used was a observation sheet, Hb Sahli and Easy Touch GHb. Average Hb levels of pregnant women who performed the examination with the used of Sahli hemoglobin was equal to 12.5400 and, while the mean Hb levels of pregnant women who carried out the examination by using the Easy Touch GHb amounted 10.0233. It was hoped the public, especially pregnant women and the health professionals can participate in reducing mortality due to anemia by examination of hb level early in pregnancy.ListenRead phonetically Keywords: Hemoglobin, Hb Sahli, Easy Touch GHb. Kesmasindo Volume 5, Nomor 1, Januari 2012, hlm. 65-74